Energy saving from small-sized urban contexts: Integrated application into the domestic water cycle. (November 2022) - Postacchini, Matteo; Di Giuseppe, Elisa; Eusebi, Anna Laura; Pelagalli, Leonardo; Darvini, Giovanna; Cipolletta, Giulia; Fatone, Francesco
Abstract: A novel approach is investigated, based on an integrated solution aiming at exploiting the energy harvestable from both drinking water reaching a municipality (or district) and wastewater flowing out from households. Global costs are also analyzed under several macroeconomic scenarios. A first experimental set was carried out using a supply system, where the mechanical power was generated using a pump as turbine (PAT). The biogas production, especially from black water discharged in a separated sewage system, was analyzed during a second set, to evaluate the anaerobic valorization of carbon sources. Several scenarios were built for small-scale urban applications, varying parameters like population and macroeconomic conditions. The produced energy changes among the scenarios: the PAT is optimized when hydraulic regulation is used, while the anaerobic digestion is optimized for decentralized system coupled to toilet operation without urine separation. Differences in energy production and costs exist between the analyzed technologies, the PAT requiring small investments for a small production, the anaerobic digestion requiring high costs for a large production. Hence, the application to urban contexts depends on the local means/needs and the size of the exploitable territory. The work also draws a potential methodology for urban planning in developing or developed countries.